Unveiling The Path To Qris Adoption: The Roles Of Perceived Ease Of Use And Risk Through Attitude Toward Using - Endarwan, Randy Eryll; Lastiati, Anies (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of perceived ease of use and perceived risk on attitude toward using and intention to use QRIS (Quick Response Code Indonesian Standard) in Jabodetabek. A quantitative research was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 201 QRIS users and analyzed using SmartPLS 3. The findings indicate that higher perceived ease of use increases both users’ attitude and intention to use QRIS. Conversely, higher users’ perceived risk reduces both their attitude toward using the system and their intention to adopt it. Moreover, it also found that users’ attitude toward using QRIS mediates the relationship between perceived variables and behavioral intention. These findings highlight the importance of educational and communication strategies to enhance positive users’ attitudes and to reduce perceived risk in order to increase QRIS adoption.